NEW MODERN DIRECTIONS AND PEDAGOGICAL TRENDS IN THE METHODOLOGY OF TEACHING THE PERSIAN LANGUAGE BASED ON FOREIGN EXPERIENCE (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes modern foreign trends in the methodology of teaching Persian. The study highlights advanced pedagogical approaches to teaching foreign languages, interactive and communicative methods, as well as didactic opportunities for using digital technologies. It also considers modern methodological strategies aimed at increasing student activity in the language teaching process, developing speech competencies, and forming practical communication skills. The article analyzes the advantages of methodological models developed on the basis of foreign experience and the possibilities of their application in the Persian language teaching process. The results of the study show that modern pedagogical approaches play an important role in increasing the effectiveness of language teaching and serve to individualize and interact the learning process.